The Role of Prison Experience on Recidivism in Kakamega County, Kenya - Evans, Oruta (2017)
Recidivism is the relapse into criminal activity and is generally measured by a former prisoner’s return to prison for a new offence. The rate of recidivism in Kenya is estimated to be about two‐thirds, which means that two‐thirds of released inmates will be re‐incarcerated after their release from prisons. As a result of this, crime by former inmates alone account for a substantial share of the current and future crimes. From the trend in the high prevalence of recidivism in Kenya, there are a staggering high number of people being incarcerated and eventually released back to the community and the high risk of re-arrest and re-incarceration is a concern for policymakers, criminologists, and those involved in corrections. High rates of recidivism result in tremendous costs both in terms of public safety and in monies spent to arrest, prosecute, and incarcerate re‐offenders. High rates of recidivism also lead to devastating social costs to the communities and families of offenders, as well as the personal costs to the offenders themselves. This made the researcher to be interested in recidivism by looking at the role of prison experience on recidivism. The study adopted survey research design. This is a type of descriptive research that adopts descriptive and fact finding enquiries of different kinds of information that describes existing phenomenon by asking individuals about their perception, attitudes, behavior or values. The study was carried out in Kakamega County, covering the three penal institutions, that is, Kakamega Male, Kakamega Female and Shikutse G.K prisons. The study population was repeat offenders found in all the three penal institutions in Kakamega County. Purposive sampling was used to identify recidivists from the general prison offender population based on the existing official prison records. a total of one hundred and forty six respondents were sampled for this study. Random sampling was used to achieve the desired representation from the study population. Questionnaires were used as data collection tools and interviews method was also utilized to collect data. Findings revealed that the longer the duration spent in prison, the worse the reentry experience since those inmates who had served longer sentences suffered the greatest reentry experiences occasioned by disintegrated families, inability to easily secure employment after release, and high chances of reoffending. Therefore the need to come up with working pre-release programs meant to enable inmates to have smooth transitions from correctional institutions to their communities by working with the offenders to develop plans, including housing, employment and participation in post-release programs. Keywords: recidivism, prisoner, re-incarceration